ANALISIS HARGA POKOK PRODUKSI DAN KEUNTUNGAN USAHA TERNAK AYAM RAS PEDAGING : STUDI KASUS PADA PT CAS DI KECAMATAN BANDAR MATARAM KABUPATEN LAMPUNG TENGAH - Irasanti, Dewi; Zakaria, Wan Abbas; Adawiyah, Rabiatul (Jurnal Ilmu Ilmu Agribisnis: Journal of Agribusiness Science, 2020)
This research aims to analyze the main production cost and the profit of chicken broiler business on partnership with PT CAS and nonpartnership. Data were collected in July 2018 at Bandar Mataram Sub- District of Lampung Tengah Regency which has been chosen purposively and the samples were drawn using purposive sampling method. The samples consisted of broiler breeders joining patrnership pattern with PT CAS and breeders who are nonpartnership. Data were analyzed using full costing and variable costing method for the main production cost and the profit of chicken broiler business. The results of this research showed that the main production cost of breeders joining the partnership was lower than that of nonpartnership breeders. The main production of partnership breeders was Rp18,158.69 with full costing method and Rp17,817.78 with variable costing method. Before fodder policy for pulling additional fodder Antibiotic Growth Promoters (AGP) and Ractopamine, livestock broiler business was profitable, but it was unprofitable afterward. Key words : broiler, main production cost, partnership